The Role of Education Systems in Preventing NEETs - Lynn van Vugt; Rolf van der Velden; Mark Levels; Christian Brzinsky-Fay (The Dynamics of Marginalized Youth, 2022)
The education system is one of the crucial institutional arrangements that shape young people's school-to-work transition. This chapter explores to what extent different aspects of education systems across countries are associated with the likelihood to become long-term NEET. The way the vocational education and training is organised differs across countries. The way education systems are providing vocational education and training depends on the combination of school- and work-based education. The chapter suggests a significant interaction with gender; women living in countries with highly stratified education systems are more likely to become long-term NEET compared to males living in countries with highly stratified education systems.
Keywords: 300